Invisible Fish - Parrott, Flora (UnderCurrents: Journal of Critical Environmental Studies, 2025)
I’m going to describe an ongoing artistic project with the title “Invisible Fish.” This project began in 2018 as a collaboration with South African writer and director Lindiwe Matshikiza. Before I begin to describe how Invisible Fish came about, I want to set the scene by reflecting on a photograph of my daughter several years ago in an aquarium, looking at a diver cleaning the tank. I’ve had this photograph on the wall of my studio ever since I took it and, in many ways, I can trace the start of the thinking for this Invisible Fish project back to this moment. [...]